The Sudan conflict: A catalyst for the spread of infectious diseases in displaced populations - Ibrahim Nagmeldin Hassan; Nagmeldin Abuassa; Mohamed Ibrahim (International Journal of Infectious Diseases)
Objective: The Sudan conflict has created a severe humanitarian crisis, displacing millions and crippling the healthcare system, leading to a resurgence of infectious diseases such as malaria, cholera, and measles. Methods: Overcrowded refugee camps with poor sanitation and limited resources have fueled outbreaks, exacerbated by disrupted immunization programs and seasonal rains. Results: Malaria is spreading rapidly due to inadequate mosquito control, while cholera outbreaks, linked to unsafe water and poor sanitation, have overwhelmed health facilities. Measles outbreaks are escalating due to low vaccination coverage, leaving vulnerable populations unprotected. The regional and global impacts are significant, as displaced populations crossing borders risk spreading diseases. Conclusion: Addressing this crisis requires urgent international collaboration to restore healthcare services, improve living conditions in camps, resume vaccination programs, and strengthen regional disease surveillance. Timely, coordinated responses are essential to mitigate health risks and protect global health security. This crisis highlights the critical need for sustained efforts to safeguard public health in conflict zones.